Current situation of Traditional Chinese Medicine nursing for patients with COVID-19 infection in post-epidemic era (后疫情时代新型冠状病毒感染患者的中医护理现状) - TONG Anran (童安然); SHEN Xianjie (沈娴杰); GUAN Huimin (官慧敏) (中西医结合护理)
The COVID-19 infection is an acute respiratory infectious disease with strong infectivity, which belongs to the category of 'epidemic disease' in Traditional Chinese Medicine. Traditional Chinese medicine nursing technology, which characterized by easy-t-operate, convenient, effective and inexpensive, is easy to be accepted by the people. In this paper, according to the different stages and symptoms after the COVID-19 infection, the application of acupuncture, moxibustion, massage, cupping, scraping, Qigong exercise and other Traditional Chinese Medicine nursing techniques were summarized to provide a basis for clinical nursing practice. (新型冠状病毒感染是具有较强传染性的急性呼吸道传染病, 属中医“疫病”范畴。中医护理技术具有“简、便、效、廉“的特点, 被广大人民群众所接受。本文根据新型冠状病毒感染后不同分期及症状, 总结针法、灸法、推拿、火罐、刮痧、气功等中医护理技术的应用现状, 为中医临床护理实践提供依据。)